Peranan Pola Pengasuhan terhadap Pemerolehan Bahasa pada Anak: Sebuah Kajian Psikolinguistik - Afry Adi Chandra (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2019)
Abstract: This study aims to see differences in language skills of children aged 25 months with children aged 24 months based on their parenting patterns. The first research subject was Arshaka Virendra (25 months) and the second research subject, namely Muhammad Firdan (24 months). Both are included in the category of 2-year-olds. This study will review aspects of the acquisition of phonology, morphosyntaxis, lexicon, and pragmatics of the two children based on differences in parenting patterns. The research approach used refers to the Indonesian children's language acquisition theory compiled by Soenjono Dardjowidjojo (2000). The procedure for collecting data was taken to refer to competent involvement and interviews with the research subjects. The data analysis technique uses an analysis of phonological, morphological, and syntactic elements tailored to the age of the two children based on Soenjono's theory of Dardjowidjojo (2000). The results of the study show that the language development process of children can be influenced by the pattern of care. Inappropriate parenting patterns can cause children to experience delays in language acquisition. Children who are less invited to communicate / interact with the caregiver can cause children's language skills to be slow to develop. Keywords: pattern of care, language acquisition, and psycholinguistics